Parity in the constitutional state. Special reference to the Spanish case - Quispe Ponce, María Candelaria (2019)
Parity is an idea that appears -inside feminist theory and praxis- aiming to eradicate the monopoly of masculine power. Its exigence in the realm of political representation is a result of the history of feminist vindications for equality, which started more than three centuries ago. In c nstitutional regimes this idea was adopted successfully -with strife- going from France to several countries in Europe and Latin America, including Peru.